Grammatical Error Analysis in English Writing Among Tourism Students: A Case Study at Sekolah Tinggi Pariwisata Mataram - Widya Suputra, I Gede (Advances in Tourism Studies, 2025)
This study investigates the types and sources of grammatical errors found in English essays written by students of Sekolah Tinggi Pariwisata (STP) Mataram. Given the contrastive structures between Indonesian (first language) and English (target language), language transfer and interlanguage phenomena are examined as contributing factors. Using a descriptive case study approach, data were collected from 90 student essays, supported by questionnaires and interviews. The analysis identified four primary types of grammatical errors: omission (40 percent), misordering (35 percent), overgeneralization (15 percent), and misinformation (10 percent), with omission emerging as the most frequent. Findings indicate that students often translate directly from Indonesian, leading to syntactic inaccuracies and structural deviations in English. Additionally, several errors reflect interlanguage development, wherein students produce forms that align with neither Indonesian nor standard English. These linguistic patterns highlight the need for targeted pedagogical interventions in English for Specific Purposes (ESP) instruction, especially in tourism and hospitality education, where effective written communication is essential. The study underscores the importance of raising students' metalinguistic awareness and integrating contrastive analysis into curriculum design to mitigate persistent grammatical errors.